In-vitro and in-vivo assessment of biocompatibility and efficacy of ostrich eggshell membrane combined with platelet-rich plasma in Achilles tendon regeneration - Omid Koohi-Hosseinabadi; Reza Shahriarirad; Amireza Dehghanian; Laleh Amini; Sajjad Barzegar; Afrooz Daneshparvar; Omid Alavi; Seyedeh-Parvin Khazraei; Saba Hosseini; Ali Arabi Monfared; Roya Khorram; Nader Tanideh; et al. (Scientific Reports)
Abstract Tendon injuries present significant medical, social, and economic challenges globally. Despite advancements in tendon injury repair techniques, outcomes remain suboptimal due to inferior tissue quality and functionality. Tissue engineering offers a promising avenue for tendon regeneration, with biocompatible scaffolds playing a crucial role. Ostrich eggshell membrane (ESM), characterized by a strong preferential orientation of calcite crystals, forms a semipermeable polymer network with excellent mechanical properties compared to membranes from other bird species, emerging as a potential natural scaffold candidate. Coupled with platelet-rich plasma (PRP), known for its regenerative properties, ESM holds promise for improving tendon repair. This study aims to evaluate the biocompatibility and efficacy of an ESM-PRP scaffold in treating Achilles tendon ruptures, employing in vitro and in vivo assessments to gauge its potential in tendon regeneration in living organisms. Ostrich ESM was prepared from pathogen-free ostrich eggs, sterilized with UV radiation and prepared in desired dimensions before implantation (1.5 × 1 cm). High-resolution scanning electron microscopy (HRSEM) was utilized to visualize the sample morphology and fiber bonding. In vitro biocompatibility was assessed using the MTT assay and DAPI staining, while in vivo biocompatibility was evaluated in a rat model. For the in vivo Achilles tendinopathy assay, rats were divided into groups and subjected to AT rupture followed by treatment with ESM, PRP, or a combination. SEM was employed to evaluate tendon morphology, and real-time PCR was conducted to analyze gene expression levels. The in vivo assay indicated that the ESM scaffold was safe for an extended period of 8 weeks, showing no signs of inflammation based on histopathological analysis. In the Achilles tendon rupture model, combining ESM with PRP enhanced tendon healing after 14 weeks post-surgery. This finding was supported by histopathological, morphological, and mechanical evaluations of tendon tissues compared to normal tendons, untreated tendinopathy, and injured tendons treated with the ESM scaffold. Gene expression analysis revealed significantly increased expression of Col1a1, Col3a1, bFGF, Scleraxis (Scx), and tenomodulin in the ESM-PRP groups. The findings of our study demonstrate that the combination of Ostrich ESM with PRP significantly enhances AT repair and is a biocompatible scaffold for the application in living organisms.